Non-motor symptoms in Multiple Sclerosis - Kubiak, Karolina; Kwiatkowska, Klaudia; Lamtych, Martyna; Badiuk, Nataliia (Journal of Education, Health and Sport, 2018)
Multiple sclerosis (MS) is the most common disease of the brain and spinal cord in young people. European doctors started talking about a new epidemic: multiple sclerosis came out on top among the diseases leading to disability of young people. In the course of the disease, an autoimmune inflammation occurs, which causes damage to the myelin layer surrounding the nerve cells. Damage occurs in numerous foci of the brain and spinal cord. Currently, there are more than 2 million patients with MS in the world [1]. Multiple Sclerosis (MS) is an autoimmune disease that leads to a demyelination process. The clinical picture of the disease is complex, and an important part of it are the non-motor symptoms, such as: dysphagia, sleep disorders, fatigue and pain, and the bladder function disorders. Some questionnaires were used to assess some of the dysfunctions listed above. The treatment of non-motor symptoms in patients with multiple sclerosis is based on the use of a various forms of therapy: pharmacotherapy, physiotherapy and surgical treatment. The aim of these is to improve the quality of life of the patient. The aim of this work is to present non-inguinal disorders occurring in patients with MS. The bibliographic databases were searched: PubMed, MedLine, Polish Medical and others. Bibliography. Articles in Polish and English were used.